The Oriented Attachment Crystal Growth Model in Hydrothermal Synthesis of Magnetite (Fe3O4) Nanoparticles - Ahmad Fadli; Amun Amri; Esty octiana sari; Sukoco Sukoco; Deden Saprudin (AMTS and Faculty of Engineering - Universitas Riau, 2019)
The magnetite nanoparticles (Fe3O4) are very promising nanomaterials to be applied as drug delivery due to their excellent superparamagnetic, biocompatibility and easily modified surface properties. Those properties are influenced by the structure and size of the material which can be controlled by studying the evolution of crystal growth. The purpose of this research is to study the evolution of crystal growth of magnetite nanoparticles in the hydrothermal system and determine the crystal growth kinetics using the Oriented Attachment Growth model. Magnetite nanoparticles were synthesized using a hydrothermal method from FeCl3, citrate, urea and polyethylene glycol at 210?C for 1 - 12 hours at a various concentration of FeCl3 (0.05 M, 0.10 M, and 0.15 M). The characterizations were conducted by X-ray Diffraction (XRD), Transmission Electron Microscope (TEM), Particle size analyzer (PSA), and Vibrating Sample Magnetometer (VSM). The XRD difractogram indicated that the magnetite was begun to form at 3.5 hours synthesis. The crystallinity and the crystal size of magnetite rose with reaction time. The diameter of magnetite crystals was in the range of 9.4-30 nm. Characterization by TEM showed that the particles were formed from a smaller particles which were then agglomerated. The PSA characterization showed that the distribution of diameter size enlarged with the enhancement of concentrations. VSM result showed that the magnetite nanoparticle has superparamagnetic properties. The magnetite crystal growth can be fitted by the Oriented Attachment Growth model with an error of 29%.